Spillover Effect of Global Financial Cycle To Asset Markets in Asean-5 Countries: A Structural VAR Approach - Andaiyani, Sri; Falianty, Telisa Aulia (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
An upsurge and volatility of capital flows to Emerging Asian Economies indicated that there is the potential effect of global financial cycle to emerging market. It provides an overview of investor risk aversion in short term investment after financial crisis 2008. Global financial cycle could have a significant impact to asset prices, including equity prices and property prices. Rey (2015) has triggered an interesting discussion about global financial cycle. She found that there was a global financial cycle in capital flows, asset prices and credit growth. This cycle was co‐moves with the VIX, a measure of uncertainty and risk aversion of the markets. Therefore, this study attempts to analyze empirically global financial cycle shocks, measured by the VIX, on equity prices and property prices in ASEAN-5, namely Indonesia, Malaysia, Singapore, Thailand and Philippines. We estimate quarterly frequency data from Q1 1990 to Q2 2016 with Structural Vector Autoregressive (SVAR) approach. The result of this study showed that global financial cycle has a negative significant impact on the ASEAN-5 asset markets, in spite of the response of shock differs by country and size. This result is consistent with ASEAN-5 as small open economies that remain vulnerable to the global factor. This study contributes to the literature in several ways. First, we identify not only cyclical expansions or contraction in asset markets but also the impact of global financial cycle to asset markets in ASEAN-5 countries. Second, we investigate whether there are heterogeneous responses of ASEAN-5 countries to global financial cycle shocks. Third, we also identify the pattern of cycle in ASEAN-5 countries.JEL Classification: F30, F37, F42Keywords: ASEAN, Asset Markets, Global Financial Cycle, SVAR